Molecular Identification of Candida Species in Bronchoalveolar Lavage Specimens of Hospitalized Children with Pulmonary Disorders - E Kashefi (Babol University of Medical Sciences, 2021)
BACKGROUND AND OBJECTIVE: Fungal agents, especially Candida species, can cause fungal and life-threatening lung infections in children. The present study was performed to identify Candida isolates obtained from bronchoalveolar lavage (BAL) specimens of children admitted to Akbar Children's Hospital in Mashhad. METHODS: In this cross-sectional study, 210 BAL specimens of hospitalized children with pulmonary disorders during 27 months (April 2018 to June 2020) were examined. Routine mycology tests including direct examination with 20% potassium hydroxide (KOH) and culture on Sabouraud dextrose agar containing chloramphenicol were performed for these specimens. The genomic DNA of Candida colonies were amplified by Multiplex PCR, and Candida species were identified based on the electrophoresis pattern. FINDINGS: The patients included 90 females (42.9%) and 120 females (57.1%) and their age range was between 2 months to 16 years and their mean age was 4.6±3.16 years. Among clinical specimens, 20 specimens (9.5%) had direct microscopic results and positive culture for Candida. Identified Candida isolates included C. albicans in 15 cases (75%), C. dubliniensis in 2 cases (10%), C. parapsilosis in 2 cases (10%) and C. tropicalis in 1 case (5%). Among the underlying factors, corticosteroid receptors and patients with neutropenia had the highest frequency (73 patients, 34.8%). CONCLUSION: The results of the study showed that C. albicans was the most common Candida isolate in the BAL specimen of hospitalized children with pulmonary disorders. Children under 4 years of age were the most affected group and pneumonia was the most common clinical form in patients with Candida infection.